Efforts to Train Public Speaking in Elementary Schools and Teacher Strategies in Building Smart Communicators - Yanto, Masti; Rizqiyah, Nailatur; Sa'i, Mad (FKIP Universitas Majalengka, 2024)
Public speaking is one of the skills that needs to be developed early on to build effective communication skills. The ability to speak in public is one of the soft skills that is needed in everyday life and the professional world. However, many students in elementary school still experience difficulties in public speaking. Therefore, this article aims to examine the strategies used by teachers in elementary schools in training public speaking to students. This research uses literature (library research) which is descriptive analysis. The procedure for obtaining data is done through document analysis. Document analysis is done by studying literature in the form of books and journal articles related to the material discussed in this article. The results show that strategies such as activity-based learning, the use of visual media, and the provision of positive feedback consistently improve students' confidence and speaking ability. This article concludes that practicing public speaking from an early age can help shape a generation that is smart, confident and able to communicate effectively.